Forest Biodiversity, Conservation and Sustainability - Ganatsas, Petros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
One of the highest priorities for human societies in the 21st century, under the challenges of predicted great environmental changes, is to conserve all kinds of biodiversity across the planet. Among all the biota that exist on Earth, forest ecosystems demonstrate a high degree of biodiversity, being thought to comprise the most diverse ecosystems, as most of the terrestrial species in the world dwell in these ecosystems. Forest biodiversity is interlinked to a web of socio-economic factors, providing an array of goods and services that range from timber and non-timber forest resources to mitigating climate change and conservation of genetic resources; therefore, it is innately linked to ecosystems and human well-being. However, in recent decades, the decrease in forest biodiversity has been a crucial and ongoing environmental issue that needs special attention and adapted ecosystem management. This Special Issue book on forest biodiversity (FB) includes a selected number of research works from all over the world dealing with emerging issues, for understanding FB and its needs for conservation, ecological processes, disturbances, climate change and ecosystems resilience, structural complexity and ecosystem functions, ecological theories and silvicultural practices, and ecosystems stability. More specifically, it includes papers focused on the indicators and methods for assessing and monitoring forest biodiversity, evaluation of practices, planting and silvicultural treatments, and management and monitoring methods, with an overall goal to provide new insights on forest biodiversity conservation, conservation of forest biodiversity in protected areas, treatments of endangered or threatened forest habitats, and sustainable management of forest resources.